Zirconium sulfonate metal organic framework material and solvent-free preparation method and application thereof
Synthesis of zirconium sulfonate metal organic framework materials through solvent-free mechanical grinding method solves the problems of high energy consumption and low yield of traditional solvent methods, and realizes the preparation and application of highly efficient and environmentally friendly zirconium sulfonate MOF, with excellent proton conductivity and catalytic activity.
Patent Information
- Application Number
- CN202510642761.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-19
- Publication Date
- 2025-07-18
AI Technical Summary
The existing Zr-MOFs synthesis methods have problems such as high energy consumption, long reaction time, large solvent usage, high treatment cost, high environmental pollution risk and low yield, which is difficult to meet the needs of large-scale industrialization.
Using solvent-free mechanical grinding, zirconium sulfonate metal organic framework material is directly synthesized by grinding 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid and zirconium nitrate under specific humidity, and then undergoing high-temperature solid phase reaction, avoiding the use of solvents.
It improves the utilization rate of raw materials, reduces the risk of environmental pollution, and improves the yield of zirconium sulfonate metal organic framework materials. The material has excellent proton conductivity and catalytic activity, which is suitable for large-scale industrial applications.
Smart Images

Figure CN120329562A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of the preparation of crystalline materials, and particularly relates to a zirconium sulfonate metal-organic framework material, a solvent-free preparation method thereof, and an application thereof. Background Art
[0002] Metal-organic frameworks (MOFs) are a class of emerging porous materials composed of metal nodes (also known as secondary building units or SBUs) and organic linkers. Their rich structural types, excellent stability, and outstanding properties have enabled significant progress in proton conduction. The main method to improve the proton conduction ability of MOFs is to introduce hydrophilic groups (such as -SO3H, -COOH, etc.) into the MOF structure to promote the binding with guest water molecules, thereby forming a dense hydrogen bond network. Protons are effectively transported along the hydrogen bond network, thereby promoting the proton conductivity of the material.
[0003] -SO3H is often introduced as a modifying group into the MOF structure. Although it has a strong hydrophilic ability when present as a functional group in the structure, due to the weak coordination ability of organic sulfonates to many metal ions in solution, the -SO3H group is generally selected as a proton source or a functional group independent on one side of the organic framework when designing functional frameworks. However, the sulfonic acid group has many advantages compared with the carboxylic acid group. Compared with carboxylic acid, the pKa value of sulfonic acid is the smallest and the acidity is the strongest, making it a good proton source. The three oxygen atoms of sulfonic acid can participate in the coordination of metal ions in different directions, thereby forming different structures (1D, 2D, or 3D) and stable MOFs. However, -SO3H is considered a poor ligand that cannot effectively displace solvent molecules from the first coordination sphere of metal ions, and there are few reports on the direct coordination of metal ions and sulfonates.
[0004] Zr-MOFs usually exhibit good stability. At present, studies have shown that introducing sulfonic acid groups into Zr-MOFs can make their structures exhibit good proton conduction ability. However, there are no relevant reports on the proton conduction of zirconium sulfonate MOFs at present.
[0005] The Chinese patent application with the publication number CN107857886A discloses a preparation method of Zr-MOF. Using an ionic liquid as a solvent and adding an appropriate amount of regulator, Zr-MOF can be rapidly prepared under room temperature stirring conditions.
[0006] The Chinese patent application with the publication number CN116535662A discloses a preparation method of a Zr-MOF material based on H2pmbda. Using ZrCl4 as a metal source and 4,6-bis(4-carboxyphenyl)pyrimidine as a ligand, and DMF as a solvent, a Zr-MOF with an interpenetrating structure is formed.
[0007] However, the above schemes all use solvent method to synthesize Zr-MOF. Traditional solvent synthesis has the following disadvantages: (1) High energy consumption and long reaction time affect the synthesis efficiency.
[0008] (2) The amount of solvent used is large, the processing cost is greatly increased, and the risk of environmental pollution is high.
[0009] (3) Low yield and poor atom economy make it difficult to meet the needs of large-scale industrialization. Summary of the invention
[0010] One of the purposes of the present invention is to solve how to improve the synthesis efficiency of Zr-MOF containing sulfonic acid ligands and improve the proton conductivity of Zr-MOF, and to provide a zirconium sulfonate metal organic framework material and a solvent-free preparation method and application thereof.
[0011] The invention prepares zirconium sulfonate metal organic framework material by a solvent-free mechanical grinding synthesis method. The solvent-free method improves the utilization rate of raw materials and the yield of the zirconium sulfonate metal organic framework material. The obtained zirconium sulfonate metal organic framework material has good proton conductivity.
[0012] The purpose of the present invention can be achieved through the following technical solutions: A zirconium sulfonate metal organic framework material, the chemical formula is [Zr(OH)2(H2O)3(NAP(COOH)2(SO3)2], the ligand is 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid, abbreviated as NAP(COOH)2(SO3H)2, and the structural formula is: ; The zirconium sulfonate metal organic framework material has a one-dimensional chain structure.
[0013] Furthermore, in the zirconium sulfonate metal organic framework material, each asymmetric unit contains a Zr 4+ ions, two and Zr 4+ Coordinated OH - ions, three and Zr 4+ The coordinated water molecule and an O atom on the sulfonate group are connected to Zr 4+ Coordinated [NAP(COOH)2(SO3)2] 2- ions; adjacent Zr 4+ Ions come from OH - The oxygen atoms of the ions are bridged and extend infinitely along the a-axis to form a one-dimensional chain Zr-secondary building unit Zr-SBU. The one-dimensional chain Zr-secondary building unit contains uncoordinated -COOH groups, and adjacent -COOH groups form hydrogen bonds in a head-to-head manner, eventually obtaining a three-dimensional crystal structure.
[0014] Furthermore, in the structure of the zirconium sulfonate metal-organic framework material, only one sulfonic acid group on each ligand coordinates with metal ions through Zr-O bonds, and the uncoordinated -COOH on the ligand forms hydrogen bonds with the uncoordinated -COOH in the adjacent layer, connecting the adjacent Zr-SBUs to form a 2D layer on the bc plane. Along with the extension of metal ions in the a-axis direction, a three-dimensional hydrogen bond framework is formed. A 1D channel surrounded by one-dimensional chain-like Zr-SBUs and uncoordinated -COOH groups is generated along the a-axis, and the channel contains sulfonic acid groups that are uncoordinated by adjacent metal ions.
[0015] A solvent-free preparation method of a zirconium sulfonate metal-organic framework material comprises the following steps: Step 1: Grind and mix 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid and zirconium oxynitrate to obtain a premix; Step 2: Perform a thermal reaction on the premix, wash the product with absolute ethanol after cooling until the supernatant is clear and colorless after centrifugation, collect the precipitate after centrifugation, and vacuum dry it at 60 - 70 °C for 12 - 16 h to obtain the zirconium sulfonate metal-organic framework material.
[0016] Further, the premix in Step 1 is specifically prepared by the following steps: In a reaction kettle, grind 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid and zirconium oxynitrate in a mortar with an air humidity of 15 - 20% for 15 - 20 min to obtain the premix.
[0017] Further, the mass ratio of 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid to zirconium oxynitrate is 38 - 44:62 - 70.
[0018] Further, the thermal reaction conditions in Step 2 are to raise the temperature to 130 - 140 °C and then react for 36 - 48 h.
[0019] An application of a zirconium sulfonate metal-organic framework material in proton conduction.
[0020] The beneficial technical effects of the present invention: (1) The present invention reports zirconium sulfonate MOF for the first time and successfully synthesizes a zirconium-based metal-organic framework material with 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid (a ligand containing sulfonic acid group and carboxylic acid group bifunctional groups) as the ligand for the first time.
[0021] (2) The zirconium sulfonate MOF described above has a one-dimensional chain-like Zr-SBU (secondary building unit), which extends along the a-axis through Zr-O bonds; a three-dimensional hydrogen bond framework is formed through hydrogen bonds between adjacent interlayer carboxylic acid groups, combining two-dimensional layered and three-dimensional topological structures; the one-dimensional chain-like Zr-SBU and the uncoordinated -COOH groups form a one-dimensional channel in the a-axis direction, and the channel contains sulfonic acid groups that are uncoordinated by adjacent metal ions. This endows the material with excellent proton conduction or catalytic activity.
[0022] (3) The present invention uses a naphthalene ring ligand containing both sulfonic acid groups (-SO3H) and carboxylic acid groups (-COOH). The sulfonic acid groups participate in coordination to form the framework, and the carboxylic acid groups enhance the structural stability through hydrogen bonds, realizing the multi-functional synergistic effect of the ligand.
[0023] (4) This application adopts a solvent-free preparation process, which is directly synthesized by grinding and mixing raw materials (without solvents) and high-temperature solid-phase reaction (100–180 °C), avoiding the pollution of organic solvents in the traditional solvothermal method. The steps are simple, environmentally friendly, and have a high yield.
[0024] The core innovation of the present invention lies in the combination of the structural design of the novel zirconium sulfonate MOF material and the solvent-free synthesis method, combining the innovation of materials science and the environmental protection of the process, providing a new idea for the development of multi-functional MOFs.
[0025] The present invention prepares the zirconium sulfonate metal-organic framework material by a solvent-free mechanical grinding synthesis method. On the one hand, the mechanical grinding method does not introduce solvents, thus avoiding the pollution of the environment by potentially harmful organic solvents and reducing the raw material cost at the same time; on the other hand, the solvent-free method theoretically incorporates all the raw materials used in the synthesis reaction into the final product, which significantly improves the yield of the reaction compared to the solvent method, meeting the requirements of atom economy and making this method applicable to large-scale industrial reactions. More importantly, the unique reaction environment provided by the mechanochemical method enables us to achieve synthesis strategies that are difficult to complete in solution, providing a new perspective for exploring new reaction mechanisms and synthesizing new materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD result diagram of the metal-organic framework material prepared in the example; Figure 2 Schematic diagram of the coordination structure of the metal-organic framework material prepared in the example; Figure 3 Schematic diagram of the pore structure of the metal-organic framework material prepared in the example; Figure 4 Infrared spectrum diagram of the metal-organic framework material prepared in the example; Figure 5SEM and EDS result diagrams of the metal-organic framework material prepared in the example; (a) and (b) are SEM diagrams of the material; (c) and (d) are EDS distribution diagrams of Zr and S elements respectively; Figure 6 Thermogravimetric test result diagram of the metal-organic framework material prepared in the example; Figure 7 XRD result diagrams of the metal-organic framework material prepared in the example after being treated under different conditions; Figure 8 Impedance test result diagram of the metal-organic framework material prepared in the example; Among them, (a) is the result of the impedance changing with temperature under 100% relative humidity; (b) is the fitting result of the activation energy; (c) is the change of proton conductivity with humidity; (d) is the impedance stability test. Detailed implementation manners
[0027] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0028] Example 1 A solvent-free preparation method of a zirconium sulfonate metal-organic framework material, comprising the following steps: S1. In a reaction kettle, grind 190 mg (0.67 mmol) of 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid and 115 mg of zirconium oxynitrate in a mortar with an air humidity of 15% for 15 minutes to obtain a premix.
[0029] S2. Transfer the premix to a Teflon-lined stainless steel autoclave, heat it to 130 °C and react for 36 hours. After cooling, wash the product with absolute ethanol until the supernatant is clear and colorless after centrifugation. Collect the precipitate after centrifugation and dry it in vacuum at 60 °C for 12 hours to obtain the zirconium sulfonate metal-organic framework material.
[0030] Example 2 A solvent-free preparation method of a zirconium sulfonate metal-organic framework material, comprising the following steps: S1. In a reaction kettle, grind 205 mg of 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid and 122.5 mg of zirconium oxynitrate in a mortar with an air humidity of 17.5% for 17.5 minutes to obtain a premix.
[0031] S2. Transfer the premix to a Teflon-lined stainless steel autoclave, heat it to 135 °C at a rate of 5 °C / min and react for 42 h. After cooling, wash the product with absolute ethanol until the supernatant is clear and colorless after centrifugation. Collect the precipitate after centrifugation and dry it in vacuum at 65 °C for 14 h to obtain the zirconium sulfonate metal-organic framework material.
[0032] Example 3 A solvent-free preparation method of a zirconium sulfonate metal-organic framework material comprises the following steps: S1. In a reaction kettle, grind 220 mg of 4,8-disulfonaphthalene-2,6-dicarboxylic acid and 130 mg of zirconium oxynitrate in a mortar with an air humidity of 20% for 20 min to obtain a premix.
[0033] S2. Transfer the premix to a Teflon-lined stainless steel autoclave, heat it to 140 °C and react for 48 h. After cooling, wash the product with absolute ethanol until the supernatant is clear and colorless after centrifugation. Collect the precipitate after centrifugation and dry it in vacuum at 70 °C for 16 h to obtain the zirconium sulfonate metal-organic framework material.
[0034] The structures of the materials obtained in Examples 1-3 are the same. The materials obtained in Examples 1-3 were characterized, and the results are as follows: Figure 1 XRD result diagram of the metal-organic framework material prepared for the example; in the freshly prepared sample, the XRD pattern shows diffraction peaks with relatively high intensities, indicating that the material has good crystallinity, providing a benchmark for subsequent performance tests.
[0035] Figure 2 Schematic diagram of the coordination structure of the metal-organic framework material prepared for the example; Figure 3 Schematic diagram of the pore structure of the metal-organic framework material prepared for the example; it can be seen that in the zirconium sulfonate metal-organic framework material, each asymmetric unit contains one Zr 4+ ion, two OH 4+ ions coordinated with Zr - ions, three water molecules coordinated with Zr 4+ ions, and one [NAP(COOH)2(SO3)2] 2- ion coordinated with Zr through the O atom on the sulfonic acid. Under the bridging action of the oxygen atoms of the OH - ions, it extends infinitely along the a-axis to form a one-dimensional chain-like Zr-secondary building unit (Zr-SBU). These one-dimensional chains contain a large number of uncoordinated -COOH groups, and adjacent -COOH groups form hydrogen bond interactions in a head-to-head form, finally obtaining a three-dimensional crystal structure and showing a one-dimensional pore structure along the a direction. There is also a series of sulfonic acids with uncoordinated adjacent metal ions arranged in this channel along the a-axis in the channel.
[0036] Figure 4 Infrared spectrum of the metal-organic framework material prepared for the example; Fourier transform infrared (FT-IR) spectroscopy verified the observed band shift at 1242 cm -1 . This is attributed to the stretching vibration of the S-O bond in the sulfonate group. Although the peak position shift is small, this may be due to the small number of coordinated sulfonic acid groups on the ligand, so the change is not obvious.
[0037] Figure 5 SEM and EDS results of the metal-organic framework material prepared for the example; SEM-EDS images confirmed the crystallographic characteristics, showing the morphology and uniform elemental distribution of the material.
[0038] Figure 6 Thermogravimetric test results of the metal-organic framework material prepared for the example; The thermal stability of the material in an air atmosphere was evaluated by thermogravimetric analysis and was stable up to a temperature of 400 °C. As shown in the figure, the first weight loss ended at 300 °C, with a total loss of 16.6%, corresponding to the loss of 5 crystal waters in one structural unit of the MOF; the second weight loss occurred at 300 °C and continued to about 500 °C, with weight losses of 4.9% and 54.1% respectively, which matched the collapse of its framework.
[0039] Figure 7 XRD results of the metal-organic framework material prepared for the example after being treated under different conditions; For the practical application value in the field of proton conduction, the stability of the MOF is very important. In the freshly prepared sample, the XRD pattern showed diffraction peaks with higher intensity, indicating that the material has good crystallinity, providing a benchmark for subsequent stability tests. We applied various conditions to this material to prove its chemical and thermal stability. We carried out PXRD measurements on the samples immersed in different solutions. The PXRD patterns remained basically unchanged, indicating that the crystal structure did not change after treatment, fully proving the chemical stability of the material.
[0040] The materials obtained in Examples 1-3 were tested for proton conduction performance: Using a customized mold, under a pressure of 1,000 kg cm -2 , about 85 mg of MOF powder was pressed into a cuboid plate (about 0.2×0.4×1.0 cm 3 ) for 3 minutes. Two surfaces of the cuboid plate (0.2×0.4 cm 2They are all fixed on silver wires using silver paste and sealed in a double-wall glass chamber. The temperature is regulated by temperature-controlled circulating water in the interlayer of the double-wall glass chamber. RH is regulated by a series of saturated salt solutions. The impedance diagrams are obtained using a Zennium pro electrochemical workstation, with a tuned frequency range of 1 Hz to 8 MHz and an alternating potential of 100 mV. The proton conductivity (σ, S cm -1 is calculated using the following formula (l, 1.0 cm; R, the measured impedance, Ω; S, ca. 0.2×0.4 cm 2 ): σ = l / (RS) The activation energy (Ea) is obtained by using the proton conductivity data between 25 and 90 °C at 100% RH and the Arrhenius equation (T, absolute temperature, K; A, pre-exponential factor; kB, Boltzmann constant): ln(σT) = lnA−Ea / (kBT) The results are as Figure 8 shown: Figure (a) shows that the impedance of the material changes uniformly with temperature; Figure (b) shows that the activation energy of the material is 0.23 eV, indicating that proton transfer mainly follows the Grotthuss mechanism (hopping mechanism, Ea < 0.4 eV). Figure (c) shows that with the increase in humidity, the conductivity of the material increases from 2.68×10 -7 S·cm -1 (33% RH) to 1.26×10 -2 S·cm -1 (98% RH). (d) To study the conductivity stability of the material, the conductivity of the sample was measured at 90 °C and 98% RH for up to 72 h, and the results show that the material maintains a basic constancy of proton conductivity during the test.
Claims
1. A zirconium sulfonate metal-organic framework material, characterized in that, The chemical formula of the molecular formula is [Zr(OH)2(H2O)3(NAP(COOH)2(SO3)2], the ligand is 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid, abbreviated as NAP(COOH)2(SO3H)2, and the structural formula is: ; The zirconium sulfonate metal-organic framework material has a one-dimensional chain structure.
2. The zirconium sulfonate metal-organic framework material according to claim 1, wherein In the zirconium sulfonate metal organic framework material, each asymmetric unit contains a Zr 4+ ions, two and Zr 4+ Coordinated OH - ions, three and Zr 4+ The coordinated water molecule and an O atom on the sulfonate group are connected to Zr 4+ Coordinated [NAP(COOH)2(SO3)2] 2- ions; adjacent Zr 4+ Ions come from OH - The oxygen atoms of the ions are bridged and extend infinitely along the a-axis to form a one-dimensional chain Zr-secondary building unit Zr-SBU. The one-dimensional chain Zr-secondary building unit contains uncoordinated -COOH groups, and adjacent -COOH groups form hydrogen bonds in a head-to-head manner, eventually obtaining a three-dimensional crystal structure.
3. The zirconium sulfonate metal-organic framework material according to claim 2, wherein In the structure of the zirconium sulfonate metal-organic framework material, only one sulfonic acid group on each ligand coordinates with metal ions through Zr-O bonds, and the uncoordinated -COOH on the ligand forms hydrogen bonds with the uncoordinated -COOH in the adjacent layer, connecting the adjacent Zr-SBUs to form a 2D layer on the bc plane. With the extension of metal ions along the a-axis direction, a three-dimensional hydrogen bond framework is formed. A 1D channel surrounded by one-dimensional chain-like Zr-SBUs and uncoordinated -COOH groups is generated along the a-axis, and the channel contains sulfonic acid groups uncoordinated by adjacent metal ions.
4. A solvent-free preparation method of a zirconium sulfonate metal-organic framework material as described in any one of claims 1-3, characterized in that, It includes the following steps: Step 1: Grind and mix 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid and zirconium oxynitrate to obtain a premix. Step 2: Carry out a thermal reaction on the premix, cool it, wash the product with anhydrous ethanol until the supernatant is transparent and colorless after centrifugation, collect the precipitate after centrifugation, and dry it under vacuum at 60-70 °C for 12-16 h to obtain the zirconium sulfonate metal-organic framework material.
5. The solvent-free preparation method of the zirconium sulfonate metal-organic framework material according to claim 4, characterized in that, The premix described in Step 1 is specifically prepared by the following steps: In a reaction kettle, grind 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid and zirconium oxynitrate in a mortar with an air humidity of 15-20% for 15-20 min to obtain a premix.
6. The solvent-free preparation method of the zirconium sulfonate metal-organic framework material according to claim 5, characterized in that, The mass ratio of the 4,8-disulfonylnaphthalene-2,6-dicarboxylic acid to zirconium oxynitrate is 38-44:62-70.
7. The solvent-free preparation method of the zirconium sulfonate metal-organic framework material according to claim 4, characterized in that, In Step 2, the thermal reaction condition is to heat up to 130-140 °C and then react for 36-48 h.
8. Application of the zirconium sulfonate metal-organic framework material according to any one of claims 1-3 in proton conduction.
Citation Information
Patent Citations
Preparation method of Zr-MOF
CN107857886A
Preparation method of Zr-MOF material constructed based on H2pmbda
CN116535662A
Cited By
Metal organic framework material with sulfonic acid and carboxylic acid groups simultaneously coordinated with chromium ions as well as preparation method and application of metal organic framework material
CN121086265A